Mass production strategy of Copepods for live feed industry - Kassim, Zaleha; Mat Nasir, Nasiratul Shahida; Hasnan, Hazwani Hanim; Jauhad, Kamaruddin (Knowledge Transfer Programme © Knowledge Transfer Centre, 2017)
Methods to cultivate live feeds in large amount have been an issue in aquaculture industry. Different farming activity will require different volume of live feeds to maintain their larval survival rate. This issue was referred to INOCEM Research Station (INOCEM) by our industrial partner, Flexible Tech Sdn. Bhd. (FTSB). Meetings were set to discuss on our collaboration target to increase the production of an important live feed, harpacticoid copepods to meet the aquaculture demand. The aim of this paper is to discuss the best strategy for copepod mass production for the industry. A pilot plant for copepod production in large scale was established in Bukit Gambir Industrial area that could accommodate 30 stacked racks with a total of 10 copepod production trays each. The production system was designed to produce about 10millions of copepods per cycle. Two Graduate Intern students (GIs) were working handin- hand with staffs from FTSB to maintain and monitor the copepod culture as well as surveying the market demand. Monthly meetings were chaired by FTSB to improve the production and marketing strategy. It was found that copepods are preferred by those aquarium industrial players (particularly the coral and ornamental fish shops) than the common aquaculture farmers. Different production and packaging techniques were used; tray and small containers for farm and aquarium shop respectively. Replication of system and production timing was found to improve the production volume. GIs were guided to deal with the potential buyers to ensure for their continued demand for supply. Generally, poor knowledge affect the acceptance level of aquaculture players on the use of copepods as live feed, thus influence the business performance of the company. Appropriate production and marketing strategy would overcome the issue and increase in sale.